Práctica clínica basada en la evidencia científica. papel del gestor de información como integrante de un equipo multidisciplinar - Cerezo Sanmartín, Margarita (Revista General de Información y Documentación, 2002)
This study analyses the figure of the Information Manager specialized in health organizations and the complete justification for his/her presence in the light of the change taking place in decision making regarding both therapy and health management. This new vision, called clinical practice based on scientific evidence, makes it possible to adopt a knowledge-based criterion of action which should be a key point in the provision of health care services in order to attain maximum quality.
Keywords: Information Manager; Scientific evidence; Health organization; Knowledge; Health care quality; Multi-disciplinary team